α-Defensin HD5 Stabilizes Human Papillomavirus 16 Capsid/Core Interactions - Neetu M. Gulati; Masaru Miyagi; Mayim E. Wiens; Jason G. Smith; Phoebe Stewart (Case Western Reserve University, 2019)
Background: Human papillomavirus (HPV) is linked to nearly all cases of cervical cancer. Despite available vaccines, a deeper understanding of the immune response to HPV is needed. Human α-defensin 5 (HD5), an innate immune effector peptide, blocks infection of multiple serotypes of HPV, including high-risk HPV16. While a common mechanism of α-defensin anti-viral activity against nonenveloped viruses such as HPV has emerged, there is limited understanding of how α-defensins bind to viral capsids to block infection. Methods: We have used cryo-electron microscopy (cryoEM), mass spectrometry (MS) crosslinking and differential lysine modification studies, and molecular dynamics (MD) simulations to probe the interaction of HPV16 pseudovirions (PsVs) with HD5. Results: CryoEM single particle reconstruction did not reveal HD5 density on the capsid surface. Rather, increased density was observed under the capsid shell in the presence of HD5. MS studies indicate that HD5 binds near the L1 and L2 capsid proteins and specifically near the C-terminal region of L1. MD simulations indicate that favorable electrostatic interactions can be formed between HD5 and the L1 C-terminal tail. Conclusions: A model is presented for how HD5 affects HPV16 structure and cell entry. In this model, HD5 binds to disordered regions of L1 and L2 protruding from the icosahedrally ordered capsid. HD5 acts to cement interactions between L1 and L2 and leads to a closer association of the L2/genome core with the L1 capsid. This model provides a structural rationale for our prior observation that HD5 interferes with the separation of L1 from the L2/genome complex during cell entry.